A new bioindicator, shell of Trachycardium lacunosum, and sediment samples to monitors metals (Al, Zn, Fe, Mn, Ni, V, Co, Cr and Cu) in marine environment: The Persian Gulf as a case. Issue 1 (December 2016) - Karbasdehi, Vahid; Dobaradaran, Sina; Nabipour, Iraj; Ostovar, Afshin; Vazirizadeh, Amir; Ravanipour, Masoumeh; Nazmara, Shahrokh; Keshtkar, Mozhgan; Mirahmadi, Roghayeh; Noorinezhad, Mohsen
Abstract Background The present work was designed to detect heavy metal contents of Al, Zn, Fe, Mn, Ni, V, Co, Cr and Cu in sediments and shells of theTrachycardium lacunosum collected in polluted and unpolluted areas along the Persian Gulf. Methods The samples were taken from surface sediments (0-10 cm) and shells ofTrachycardium lacunosum in two separated areas (polluted and unpolluted) in northern part of the Persian Gulf, Asaluyeh Bay, during summer 2013. The prepared samples were analyzed by inductively coupled plasma-optical emission spectrometry (ICP-OES). Results Based on the results, all measured metals including Al, Zn, Fe, Mn, Ni, V, Co, Cr and Cu were meaningfully higher in the sediment samples of polluted area compared to unpolluted area and the order of metal concentrations in the sediment samples were Cr > Co > V > Ni > Zn > Cu > Fe > Al > Mn in polluted area. In the case of shell samples ofTrachycardium lacunosum, polluted area contained significantly higher contents of Al, Zn, Fe, Mn, Ni, Co, Cr and Cu compared to unpolluted area and the order of metal concentrations in the shell samples were Fe > Zn > Al > Mn > Cu > Cr > Ni > Co in the polluted area. Conclusion It was concluded that shells of theTrachycardium lacunosum can be used as a suitable bioindicator for heavy metals in the aquatic environment. Results confirmed that due to the possible contaminations by oil and gas activities near the polluted area perennial monitoring and mitigation measures is extremely necessary.